AUTHORS’ AFFILIATION INFLUENCE TOWARDS RHETORICAL MOVES AND LINGUISTIC FEATURES OF REJECTED RAAS - Ayu Intan Harisbaya; Eri Kurniawan; Arif Husein Lubis (English Review: Journal of English Education, 2023)
An abstract is the selling point of a research article (RA), due to the fact that it can help the readers and particularly journal reviewers in selecting which RAs are remarkable to be read further and accepted. A plethora of research has analyzed the rhetorical moves and linguistic features of accepted RAAs. Nevertheless, almost none of them have explored the rejected one, based on the authors’ affiliation. Invoking Hyland’s (2000) rhetorical move model as the main instrument, this study intends to dismantle and fill up those lacunas by utilizing 31 rejected RAAs in total from Indonesian Journal of Applied Linguistics (IJAL), submitted in 2019, 2020, and 2021. The data were then separated into the same affiliation (13 abstracts) and different affiliation (18 abstracts) groups in order to find the commonality and discrepancy in the rhetorical move and linguistic features (i.e. tenses, voice, and grammatical subjects). As a result, the authors’ affiliation had some influences on the structure of rhetorical moves of RAAs and the accommodation of linguistic features in each move. It also appeared that there were some primary shortcomings found in the rejected abstracts as compared to the accepted ones. This study can be adopted as the reference for future research in rhetorical moves analysis, specifically regarding the authors’ affiliation and rejected RAAs.